SOPHIA: Soft Orthotic Physiotherapy Hand Interactive Aid - McConnell, Alistair C.; Vallejo, Marta; Moioli, Renan Cipriano; Brasil, Fabricio L.; Secciani, Nicola; Nemitz, Markus P.; Riquart, Cecile P.; Corne, David W.; Vargas, Patricia A.; Stokes, Adam A. (Frontiers in Mechanical Engineering, 2017)
This work describes the design, fabrication and initial testing of a Soft Orthotic Physiotherapy Hand Interactive Aid (SOPHIA) for stroke rehabilitation. SOPHIA consists of: 1.) A soft robotic exoskeleton, 2.) A microcontroller based control system driven by a Brain-Machine Interface (BMI), and 3.) A sensorised glove for passive rehabilitation. In contrast to other rehabilitation devices, SOPHIA is the first modular prototype of a rehabilitation system that is capable of three tasks: aiding extension based assistive rehabilitation, monitoring patient exercises, and guiding passive rehabilitation. Our results show that this prototype of the device is capable of helping healthy subjects to open their hand. Finger extension is triggered by a command from the BMI, while using a variety of sensors to ensure a safe motion. All data gathered from the device will be used to guide further improvements to the prototype, aiming at developing specifications for the next generation device, which could be used in future clinical trials.